MEASURING HUMAN DEVELOPMENT: AN ALTERNATIVE INDEX TO THE HDI-2010. SPECIAL FOCUS ON LATIN AMERICAN COUNTRIES - Veres Ferrer, Ernesto J. (Investigación Económica, 2015)
This paper presents an alternative index to the Human Development Index (HDI). It uses the same statistical information as the HDI. We obtain an alternative ranking of countries according to their human development. The new index is not grounded in the values of the indicators on which it is based, but rather on the position that each indicator has with respect to other indicators. Then each indicator is classified in the corresponding quartile. The design of this new index downgrades indicators if they fall into lower development quartiles. An application focuses particularly on Latin American countries.